Business continuity management lessons learned from COVID-19 - Goldstein, Monica; Flynn, Sherri (Journal of business continuity & emergency planning, 2022)
This paper reviews how the COVID-19 pandemic has impacted established best practices in the field of business continuity management (BCM). It reviews the lessons learned and provides suggestions on how business continuity programmes need to evolve in order to reflect the changed landscape. By walking through the BCM life cycle, the paper considers the various changes required at each phase of the BCM programme.